The Armadillo as a Model for Leprosy Nerve Function Impairment: Preventative and Therapeutic Interventions - Pena, Maria Teresa; Lahiri, Ramanuj; Ebenezer, Gigi J.; Wheat, Stephen W.; Figarola, John; Truman, Richard W.; Adams, Linda B. (Frontiers in Medicine, 2022)
Mycobacterium leprae infection of peripheral nerves and the subsequent nerve function impairment (NFI), especially in response to reactional episodes, are hallmarks of leprosy. Improved treatments for M. leprae-induced nerve injury are needed, as most if not all of the disability and stigma associated with leprosy arises from the direct or indirect effects of NFI. Nine-banded armadillos (Dasypus novemcinctus), like humans, exhibit the full clinical spectrum of leprosy and extensive involvement of the peripheral nerves. In this study, state-of-the-art technology was used to compare nerve function between uninfected and M. leprae-infected armadillos. Motor nerve conduction velocity (MNCV) and compound muscle action potential (cMAP), which measure changes in the rate of impulse conduction velocity and amplitude, revealed a progression of impairment that was directly correlated with the duration of M. leprae infection and enabled development of an objective nerve impairment scoring system. Ultrasonography accompanied by color Doppler imaging detected enlargement of the M. leprae-infected nerves and increased vascularity, possibly due to inflammation. Assessment of epidermal nerve fiber density (ENFD), which shows a length-dependent innervation in armadillos that is similar to humans, identified small fiber degeneration early after M. leprae infection. Staining for neuromuscular junction (NMJ) integrity, which is an indicator of signal transduction efficiency into skeletal muscle, discerned a markedly lower number and structural integrity of NMJ in M. leprae-infected armadillo footpads. These tools for assessing nerve injury were used to monitor the effects of intervention therapy. Two potential neuro-protective drugs, ethoxyquin (EQ) and 4-aminopyridine (4-AP), were tested for their ability to ameliorate peripheral nerve injury in M. leprae-infected armadillos. 4-AP treatment improved MNCV, cMAP, and EFND compared to untreated animals, while EQ had less effect. These results support the armadillo as a model for M. leprae-induced peripheral nerve injury that can provide insights toward the understanding of NFI progression and contribute to the preclinical investigation of the safety and efficacy of neuro-preventive and neuro-therapeutic interventions for leprosy.